Analysis of Knowledge Level, Self-Efficacy, and Self-Management among Type 2 Diabetes Mellitus Patients in Rural Areas of Aceh Province - Rihhadatul Aisy; Asniar Asniar; Teuku Tahlil (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Diabetes mellitus (DM) is a chronic disease and a major global health challenge. Uncontrolled hyperglycemia can cause microvascular and macrovascular complications. Patients' knowledge, self-efficacy, and self-management abilities, which vary in rural communities, influence effective management. Objective: This study aimed to analyze knowledge, self-efficacy, and self-management among patients with type 2 DM in rural areas of Aceh Province. Method: A cross-sectional design was used involving 72 respondents. Data were collected using structured questionnaires: DKQ-24 for knowledge, DES-SF for self-efficacy, and the Diabetes Mellitus Self-Management Behavior questionnaire for self-management. Result and Discussion: Descriptive and crosstab analyses were conducted. The mean score of knowledge was 13.60 (SD=2.516), self-efficacy 25.63 (SD=3.510), and self-management 73.54 (SD=10.911). The findings indicate that knowledge, self-efficacy, and self-management levels among patients with type 2 DM in rural Aceh remain varied and suboptimal. Conclusion: These findings highlight the importance of strengthening education and patient empowerment strategies tailored to rural settings. Improving access to continuous support from healthcare providers and communities may enhance treatment adherence, promote healthier behaviors, and reduce long-term disease burden locally